2004
DOI: 10.1111/j.1744-618x.2004.tb00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Diagnostic Accuracy Using an Evidence‐Based Nursing Model

Abstract: Use of an EBM to teach nurses how to ask relevant diagnostic questions and provide a framework for nurse educators to teach evidenced-based practice may lead to developing more competent diagnosticians and improving diagnostic accuracy in nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 17 publications
(17 reference statements)
0
17
0
3
Order By: Relevance
“…founded on the taxonomy adopted by the service (2) ; however, they were incompletely formulated, since the related or risk factors were present in 133 (98.5%) and 39 (28.8%) stated their defining characteristics incompletely; for about 14% of the subjects, no defining characteristic was considered; it is worth remembering that 42% of the observed diagnoses were real, i.e., they should also present defining characteristics. These data suggest that nurses are The accuracy in reaching a diagnosis has been reported as a relevant difficulty (6,18) ; and has varied considerably (21) . A study reported that 30% of the analyzed nursing diagnoses presented poor accuracy, according to the specialists' evaluation (22) .…”
Section: Resultsmentioning
confidence: 95%
“…founded on the taxonomy adopted by the service (2) ; however, they were incompletely formulated, since the related or risk factors were present in 133 (98.5%) and 39 (28.8%) stated their defining characteristics incompletely; for about 14% of the subjects, no defining characteristic was considered; it is worth remembering that 42% of the observed diagnoses were real, i.e., they should also present defining characteristics. These data suggest that nurses are The accuracy in reaching a diagnosis has been reported as a relevant difficulty (6,18) ; and has varied considerably (21) . A study reported that 30% of the analyzed nursing diagnoses presented poor accuracy, according to the specialists' evaluation (22) .…”
Section: Resultsmentioning
confidence: 95%
“…Some authors tried to categorize the DCs presented for these diagnoses in the NANDA‐I 1999/2000 version into critical characteristics and noncritical characteristics in an attempt to organize the suggested list (Adams et al., 1997; Levin & Krainovich‐Miller, 1999). Whitley (1994) and Levin, Lunney, and Krainovich‐Miller (2004) proposed a categorization of the DCs for anxiety, such as affective, physiological, behavioral, and cognitive characteristics; subjective and objective characteristics were proposed for fear. These studies were regarded as significant in refining both diagnoses and led to a change in their definitions and the list of DCs.…”
Section: Discussionmentioning
confidence: 99%
“…The interpersonal skills have to do with the capacity that the nurse must have in relating well with the patients and family members in order to confirm the data gathered and the interpretation of those data. Efforts directed at helping nurses increase their diagnosing skills will result in more precise diagnoses (Levin, Lunney, & Krainovich‐Miller, 2004; Lunney, 2004).…”
Section: Discussionmentioning
confidence: 99%